2016
DOI: 10.1111/nph.14072
|View full text |Cite
|
Sign up to set email alerts
|

Loss‐of‐function of Arabidopsis receptor‐like kinase BIR1 activates cell death and defense responses mediated by BAK1 and SOBIR1

Abstract: The Arabidopsis receptor-like kinase (RLK) BIR1 (BAK1-INTERACTING RECEPTOR-LIKE KINASE 1) functions as a negative regulator of plant immunity. Previous work showed that loss-of-function of BIR1 leads to constitutive activation of cell death and defense responses. These autoimmune phenotypes are partially dependent on another RLK, SOBIR1. In order to identify additional components involved in the BIR1-regulated plant defense signaling pathway, a suppressor screen was carried out in the bir1-1 pad4-1 mutant back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(122 citation statements)
references
References 36 publications
4
112
0
6
Order By: Relevance
“…The proteins from these networks were activated, indicating an increase in the ABA response in cassava leaves under stress treatments, which is consistent with our results in Table 2 . Previous work showed that BIR1 functions as a negative regulator of plant immunity through regulating multiple plant resistance signaling pathways (Liu et al, 2016). MGT3 was involved in transporting magnesium, which acted as a key osmoticum maintaining growth in low calcium concentrations in plants (Conn et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The proteins from these networks were activated, indicating an increase in the ABA response in cassava leaves under stress treatments, which is consistent with our results in Table 2 . Previous work showed that BIR1 functions as a negative regulator of plant immunity through regulating multiple plant resistance signaling pathways (Liu et al, 2016). MGT3 was involved in transporting magnesium, which acted as a key osmoticum maintaining growth in low calcium concentrations in plants (Conn et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…BIR1 interacts constitutively with BAK1 but not with other RKs 288 such as FLS2, PEPR1 and CLAVATA and plays a role in cell death control but not in 289 BR or MAMP signaling (Gao et al, 2009;Liu et al, 2016). BIR2 also constitutively 290 interacts with BAK1 and is released after ligand binding to BAK1-interacting RKs, 291 allowing for the interaction of BAK1 with the ligand-bound RKs.…”
Section: Botrytis-induced Kinase1 (Bik1) Which In Turn Phosphorylatementioning
confidence: 99%
“…Analysis of suppressor mutants of lsd1 revealed that ADR1, ADR1-L1, and ADR1-L2 are required for the lesion mimic phenotype of lsd1 (Bonardi et al, 2011), suggesting that NB-LRR-mediated defense responses are activated in the mutant. Studies on suppressors of bir1-1 revealed that loss of BIR1 leads to activation of immune responses mediated by RLKs BAK1 and SUPPRESSOR OF BIR1 (SOBIR) 1 (Gao et al, 2009; Liu et al, 2016). …”
Section: Applications Of Autoimmune Mutants In Genetic Analysis Of Plmentioning
confidence: 99%